Development of Scratch Learning Media to Improve Scientific Literacy and Computational Thinking in Primary Education in The Society 5.0 Era - Berlian, Mery; Arsad, Nurazidawati Mohd; Hardila, Dilva; Yovita, Yovita; Nasution, Desi Nori (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Learning media are one of the most important components in the implementation of learning both inside and outside the classroom. In this era, learning media must be technology-based and have a good pedagogic approach, as well as complete and in-depth material content. From an analysis of conditions in the field and a review of several articles, researchers wanted to develop a learning medium in the form of a Scratch-Based E-Module. Methodology-This study is an R&D using the ADDIE model seen from the practical aspects, involving 100 (41%) teachers, 100 (42%) university students, and 40 (17%) students. Data were collected via a google form with an assessment component consisting of several aspects, namely (1) ease of use, (2) presentation, (3) readability, and (4) the role of the media. From the data obtained, as a whole, the product provides information and technology-based teaching material facilities with a combination of videos, text, images, coding, games, and QR-Code. Findings- This product meets the validity criteria of 77% with the